Buried treasure : discovering and implementing the value of corporate social responsibility - Wall, Caleb (Sheffield, U.K. : Greenleaf Pub., 2008)
With business under unprecedented pressure from a range of stakeholders to engage in corporate social responsibility (CSR), those working in dirty industries, developing countries and the extractive sector are finding themselves exposed to great strategic risks. Many of these companies are endeavouring to practise CSR and sustainability, but lack the knowledge to do so convincingly. Much of what has been published to date tells companies they must 'do' CSR, without explaining how best to implement CSR-related policies and why this is very much in the corporate interest. Buried Treasure sets out in a series of case studies from different industries around the world a clear demonstration of how it is possible to create 'shared value' for companies, communities and other stakeholders by putting CSR at the core of the business model.
Front cover; Half-title; About the author; Title page; Copyright page; Contents; Figures, tables and boxes; Foreword; Acknowledgements; 1. The opportunity of corporate responsibility; 2. Leverage your core competences; 3. Collaborate based on common values; 4. Operate globally -impact locally; 5. Evolution to revolution; 6. Governments and the changing business climate; 7. Non-governmental organisations; 8. Creating shared value: the next steps; Acronyms and abbreviations; Endnotes; References; Index; Back cover.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Social responsibility of business; Issues management -- Economic aspects; Economic value added; Electronic books